Improving Understanding of Fraction Concepts Through Problem-Based Learning in Elementary Schools - Cahyaningsih, Ujiati; Salimi, Moh; Nahdi, Dede Salim; Jatisunda, Mohamad Gilar; Rasyid, Abdur (Papanda Publisher, 2025)
Fraction concepts represent one of the most challenging mathematical domains in elementary education, with persistent international difficulties in student comprehension despite their fundamental importance for advanced mathematical proficiency. Traditional instructional methods emphasizing rote memorization have consistently demonstrated limitations in fostering deep conceptual understanding. This study investigated the effectiveness of Problem-Based Learning (PBL) in enhancing elementary students' fraction understanding compared to conventional teaching approaches. A quasi-experimental design with non-equivalent control groups was employed, involving 38 elementary students from nine schools. The experimental group (n=16) received PBL instruction featuring authentic, real-world fraction problems requiring collaborative solution strategies, while the control group (n=22) participated in traditional direct instruction. Data collection utilized pre-test and post-test assessments measuring conceptual and procedural fraction understanding, structured classroom observations documenting engagement and learning behaviors, and student feedback questionnaires capturing motivation and confidence levels. The experimental group demonstrated substantial improvement with a mean increase of 33.25 points (Cohen's d = 3.47), while the control group showed minimal gains (7.78 points, Cohen's d = 0.91). Paired-sample t-tests confirmed statistically significant differences (p < 0.001) favoring the experimental group. Qualitative analysis revealed enhanced collaborative learning, mathematical discourse, and problem-solving confidence among PBL participants. Student motivation scores were significantly higher in the experimental group (M = 4.31 vs. 3.18). Results provide robust empirical evidence supporting PBL's superiority over traditional methods for fraction instruction. The findings validate constructivist learning principles and demonstrate that authentic problem-solving contexts facilitate deeper conceptual understanding, multiple representational thinking, and sustained student engagement, addressing persistent challenges in elementary mathematics education.